FTMSK invigilation timetabling system (FITS) / Abdul Halim Mat Noh - Mat Noh, Abdul Halim (2005)
In this project, a powerful problems solution of genetic algorithm method is provided to solve invigilation timetabling problems. This combines with the satisfaction constraints of hard and soft constraints to get to the optimal solutions. All these constraint will go through the evolutionary process such as reproduction, selection, and mutation to get the fitness chromosomes. The fitness chromosome is definitely the optimal solutions that later will develop the invigilation timetable. Finally, a system called FITS is presented to develop the invigilation timetable.